A magyar-szlovák határ menti kapcsolatok az Ister-Granum Eurorégió területén: A Mária Valéria Nemzetközi Borút lehetősége - Hartl, Mónika (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
In my research I am looking for the prominent opportunities of the Slovak-Hungarian border. I would like to stress that the development of the regional economy is absolutely necessary regarding the improvement of the tourism sector since it will create opportunities to retail local goods. In order to improve tourism it is also vital to have a high standard in infrastructure and in services. The border destinations can be very tempting for investing capital and in this way the multiplicator effect can be realised. I also examine the motivations to cross the border. I try to call attention how underused the euro region's potentials are and that it is essential to form a unified tourism marketing and marketing communication. Mária Veléria International Wine Way could provide us with a wide range of solutions.